Weak and strong type estimates for fractional integral operators on Morrey spaces over metric measure spaces - Sihwaningrum, Idha; Sawano, Yoshihiro (Eurasian Mathematical Journal, 2013)
We discuss here a weak and strong type estimate for fractional integral operators on Morrey spaces over metric measure spaces, where the underlying measure does not always satisfy the doubling condition.